AN INVESTIGATION OF STUDENT'S PERFORMANCE IN USING COMPOUND-COMPLEX SENTENCES IN WRITING AT EFL CLASSROOM - Daud, Abdulhalim; Firmansyah, Firmansyah; Octasary, Magvirah (Universitas Khairun, 2024)
This study investigates the challenges faced by English as a Foreign Language (EFL) students in using compound-complex sentences in their writing. The research aims to shed light on the difficulties encountered by EFL students when combining independent and dependent clauses with coordinating conjunctions to form compound-complex sentences. The study also explores the impact of mastering compound-complex sentences on EFL students' comprehension of literature texts. Through a mixed-method approach, including tests and interviews, the research analyzes the performance of EFL students in organizing complex and compound sentences and their ability to convert compound sentences into compound-complex ones. The findings reveal the obstacles EFL students encounter in structuring sentences and developing ideas in paragraphs, particularly when attempting to use compound-complex sentences. The study underscores the importance of sentence structure in effective writing and its influence on text clarity, coherence, and overall impact. The implications of this research extend to teaching and learning strategies in EFL classrooms, aiming to enhance students' writing capabilities and comprehension of literature texts.